Phytochemicals and some Heavy Metal detection in Ripe Healthy Mesocarp Raphia hookeri fruits - Okungbowa , F. I.; Esiegbuya, O. D.; Okogbenin , O. B. (Nigerian Journal of Pharmaceutical and Applied Science Research, 2020)
A study of the phytochemical and heavy metal composition of ripe R. hookeri fruits was carried out using the Buck 200 Atomic Absorption Spectrophotometer (AAS) method described by the Association of Official Analytical Chemists. The study revealed the presence of phytochemicals such as phenols, flavonoids, alkaloids, saponin, oxalate and quinines at 0.0302%, 23%, 4% 0.0185%, 0.0225% and 0.015% respectively. Tannin was not detected. The heavy metals were copper (1.93ppm), cadmium (1.43ppm) and chromium (1.93ppm). Lead was not detected. Oxalic acid and the heavy metal cadmium detected in the ripe healthy mesocarp of R. hookeri fruits are undesirable components in human food because of their potential risk in causing urinary disease and increasing the nutritional toxic level of food samples. It is therefore recommended that the consumption of R. hookeri fruit be discouraged due to its possible health risk. However, other economic benefits due to the presence of phytochemicals, such as its use in herbal medicine, tissue culture, as a purgative, anti-microbial, anti-tumor and anti-cardiovascular agents can be exploited.